SYNTHESIS OF CARBON DOTS FROM BANANAâS PEDUNCLE AND ITS ANTIBACTERIAL ACTIVITY AGAINST XANTHOMONAS ORYZAE PV. ORYZAE (XOO) - Hari, Ivony
Bacterial leaf blight (HDB) on rice caused by Xanthomonas oryzae pv. oryzae (Xoo) can attack all phases of rice growth and cause yield losses of up to 40%. Antibacterial substances that are non-toxic and biodegradable can overcome HDB disease. One alternative antibacterial substance is carbon dots (c-dots). This research focuses on synthesizing c-dots from a banana’s peduncle biomass residue as an antibacterial material. C-dots were synthesized by microwave and hydrothermal methods. Transmission Electron Microscopy (TEM) images show that c-dots have been successfully synthesized with spherical shapes and particle sizes from 1.7 nm to 6 nm. The diffraction pattern results showed that the resulting c-dots had a poly-nanocrystalline structure with lattice gap widths between 0.105 nm and 0.109 nm. The photoluminescence properties of c-dots were evaluated by irradiating UV light with an excitation wavelength of 420 nm, resulting in an emission wavelength of 519-520 nm. The resulting glow is bluish green. Functional group analysis with Fourier Transform Infra-Red (FTIR) showed that the c-dots had the functional group O-H at 3415 nm-1, C-H at 2960 nm-1, and C=O at 1634 nm-1. The antibacterial properties of c-dots were evaluated using the Total Plate Count (ALT) method. C-dots show up to 95% reduction of bacterial colonies. C-dots synthesized by hydrothermal method had better antibacterial properties than c-dots produced by microwave. This study's results indicate that c-dots can be used as an alternative antibacterial substance to treat HDB disease.